Association of mitral annulus calcification, aortic valve sclerosis and aortic root calcification with abnormal myocardial perfusion single photon emission tomography in subjects age ≤65 years old - Jeon, Doo-Soo; Atar, Shaul; Brasch, Andrea V; Luo, Huai; Mirocha, James; Naqvi, Tasneem Z; Kraus, Robert; Berman, Daniel S; Siegel, Robert J (Journal of the American College of Cardiology, 2001)
OBJECTIVES We examined the hypothesis that mitral annulus calcification (MAC), aortic valve sclerosis (AVS) and aortic root calcification (ARC) are associated with coronary artery disease (CAD) in subjects age ≤65 years. BACKGROUND Mitral annulus calcification, AVS and ARC frequently coexist and are associated with coronary risk factors and CAD in the elderly. METHODS We studied 338 subjects age ≤65 years who underwent evaluation of chest pain with myocardial perfusion single photon emission computed tomography (SPECT) and a two-dimensional transthoracic echocardiogram for other indications. The association of MAC, AVS and ARC with abnormal SPECT was evaluated by using chi-square analyses and logistic regression analyses. RESULTS Compared with no or one calcium deposit and no or one coronary risk factor other than diabetes, multiple (≥2) calcium (or sclerosis) deposits with diabetes or multiple (≥2) coronary risk factors were significantly associated with abnormal SPECT in women age ≤55 years old (odds ratio [OR], 20.00), in women age >55 years old (OR, 10.00) and in men age ≤55 years old (OR, 5.55). Multivariate analyses identified multiple calcium deposits as a significant predictor for an abnormal SPECT in women (p < 0.001), younger subjects age ≤55 years (p < 0.05) and the total group of subjects (p < 0.01). CONCLUSIONS When coronary risk factors are also taken into consideration, the presence of multiple calcium deposits in the mitral annulus, aortic valve or aortic root appears to be a marker of CAD in men ≤55 years old and women.